Transcendent and Transcendental Time Perspective Inventory - Timoszyk-Tomczak, Celina; Bugajska, Beata (Frontiers in Psychology, 2019)
The purpose of this paper is to propose a tool to examine the transcendent and transcendental time perspective (TTTP). The inspiration to develop the scale was a 10-item Transcendental Time Perspective Inventory by Philip G. Zimbardo and John N. Boyd, as well as by Lars Tornstam’s gerotranscendence theory. The analysis of life from death to eternity is an interesting, heterogeneous and difficult subject of study. The proposed TTTP inventory can be utilised to investigate the future that extends beyond the frames of a personal time perspective, beyond the individual’s death as well as beyond the recognised, standard ways of understanding oneself, other people and the world. The inventory refers to changes of quantitative and qualitative nature relating to what is going to happen. It is composed of two sub-scales: the transcendental future and the transcendent future. The paper outlines the psychometric values of the qualities of the inventory, its validity and accuracy based on such indicators as the discriminative of items, the Cronbach alpha index for each of the sub-inventories and the confirmatory factor analysis. The study findings come from analyses conducted on a group of 211 elderly subjects (the average age of 65; 70% women, 30% men). Additionally, the paper presents data on the accuracy of the external scale. The data are interpreted in the light of the time perspective theory as well as the existing studies.